Differences in prevalence and associated factors of underweight and overweight/obesity according to rural–urban residence strata among women of reproductive age in Bangladesh: Evidence from a cross-sectional national survey - Hashan, Mohammad Rashidul; Gupta, Rajat Das; Day, Brendan; Al Kibria, Gulam Muhammed (BMJ, 2022)
This article was published in BMJ Open [ © Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2019-034321 The Journal's website is at: https://bmjopen.bmj.com/content/10/2/e034321